Fibrillary Glomerulonephritis and Monoclonal Gammopathy: Potential Diagnostic Challenges - Da, Yi; Goh, Giap Hean; Lau, Titus; Chng, Wee Joo; Soekojo, Cinnie Yentia (Frontiers in Oncology, 2022)
Fibrillary glomerulonephritis (FGN) is a rare glomerular disease featured by the randomly arranged 12-24nm fibrils under electron microscopy. Up to 10% of FGN patients have monoclonal gammopathy. However, distinguishing between FGN as MGRS, versus FGN from other causes with incidental monoclonal gammopathy of undetermined significance (MGUS) can be challenging, as the current way of demonstrating monoclonality is flawed due to 1) suboptimal sensitivity of kappa staining by immunofluorescence in frozen tissue (IF-F) as compared to pronase-digested paraffin sections (IF-P), causing incorrect labeling of light chain restriction; 2) unavailability of IgG subtyping in some centers; 3) unavailability of tests demonstrating the monoclonality of highly variable VH or VL domains in immunoglobulin structure in clinical use. The discovery of DnaJ homolog subfamily B member 9 (DNAJB9) allows diagnosis for FGN with less reliance on EM, and the summary of recent studies revealed that genuine MGRS is extremely rare among FGN. Further research integrating IF-P, IgG subtyping, VH or VL domain monoclonality confirmation, and DNAJB9 as diagnostic modalities, with corresponding clinical data including treatment response and prognosis, is required, for a better understanding of this area.